Do barro às panelas de cozer : variabilidade das cerâmicas artesanais na senzala da Fazenda do Colégio dos Jesuítas, Campos dos Goytacazes - RJ. - Paula de Aguiar Silva Azevedo (2019)
During the campaigns of archaeological excavations in the senzala of the College of the Jesuits, Campos dos Goytacazes (RJ) pottery ceramics of local production had been found. The apparent homogeneity of the sample was slowly deconstructed with a detailed analysis revealing the stylistic and morphological differences over time and space. The analysis involved a more integrated view of the ceramic style, encompassing decorative, formal and technical aspects, based on a series of attributes. Given the contrasts found between the excavated areas, the hypothesis formulated was that groups within this community made different choices about their material culture. The chronological scale presented continuities and ruptures in the ceramic vessels' choices. What at first seemed to be a homogeneous sample, presented, in fact, several particularities, which included the styles of wings, the decorations within a specific chronology, and the morphological variability over time and space. The contrasts and material relations between the slave community and the headquarters of the big house are here discussed. A reflection over the relationship between ceramics, food practices and the maintenance of ancestral practices through the maintenance of this ceramic tradition is likewise presented in this dissertation.